2008
DOI: 10.1093/rheumatology/ken397
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atherogenic and anti-inflammatory properties of high-density lipoprotein are affected by specific antibodies in systemic lupus erythematosus

Abstract: Objective. To determine whether antibodies against high-density lipoprotein (aHDL) and apolipoprotein A-I (aApo A-I) interfere with the anti-atherogenic functions of high-density lipoprotein (HDL) and relate to disease activity and damage in SLE. Methods. Seventy-seven SLE patients were compared with an age-and sex-frequency matched control group. Immunoglobulin G (IgG) aHDL, IgG aApoA-I, soluble vascular cell and intracellular cell adhesion molecules (VCAM-1 and ICAM-1, respectively) were measured by ELISA, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 43 publications
6
83
0
Order By: Relevance
“…In spite of the fact that the absence of differences in total antioxidant capacity between SLE and controls is in agreement with previous studies in SLE subjects (38,39), there is no consensus about it in the literature. While some authors have reported lower levels in autoimmune diseases (40,41), others have found higher ones (42). Since it has been reported an increase in the serum levels of total antioxidant capacity to act against oxidative stress (42), it is likely that this parameter is dependent on the oxidative stress status.…”
Section: Discusionmentioning
confidence: 98%
“…In spite of the fact that the absence of differences in total antioxidant capacity between SLE and controls is in agreement with previous studies in SLE subjects (38,39), there is no consensus about it in the literature. While some authors have reported lower levels in autoimmune diseases (40,41), others have found higher ones (42). Since it has been reported an increase in the serum levels of total antioxidant capacity to act against oxidative stress (42), it is likely that this parameter is dependent on the oxidative stress status.…”
Section: Discusionmentioning
confidence: 98%
“…In the context of autoimmune diseases, HDL represents a likely target for auto-reactivity. Elevated levels of anti-HDL have been reported in PAPS in association with decreased PONa and HDL [60,61]. Moreover low levels of Apo A and HDL inversely related to C-Reactive Protein (CRP) in keeping with an anti-inflammatory activity of these lipoproteins in PAPS [61].…”
Section: Antibodies Against High Density Lipoprotein and Atherosclerosismentioning
confidence: 99%
“…Thus anti-Apo A-1 antibodies, in a similar manner to anti-HDL, seem to interfere with the antiatherogenic properties of HDL, increasing oxidative stress and, in turn, the risk of atherosclerosis in patients with SLE [80].…”
Section: Apolipoprotein A-1mentioning
confidence: 99%